Tunable Class-F high power amplifier at X-Band using GaN HEMT - Ceylan, Osman; Yagci, Hasan Bülent; Paker, Selçuk (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2018)
Class-F type amplification stands on proper termination of harmonics such as short for even harmonics and open for odd harmonics. Moreover, termination of only the first few harmonics is practical for high-frequency circuits, while obtaining satisfactory short and open terminations at high frequencies is a challenging design issue. In the present study, a topology of harmonics termination for Class-F load network with 2nd and 3rd harmonics and its relative analytical analysis are presented. The proposed output termination structure for Class-F type amplification provides an improved short termination of 2nd harmonic; therefore, the efficiency of the power amplifier increases. In addition, the topology implemented with the microstrip lines has a tunable structure, and it is suitable for very high-frequency applications due to its straightforward architecture. An X-Band high power amplifier for a small satellite transmitter is designed and fabricated with the proposed method. A 0.25 mu m GaN on SiC HEMT having a total gate width of 1.25 mm is used. The PA achieves the peak PAE of 55% at 8.1 GHz while the output power is 36 dBm at the 3 - dB compression point. The Class-F PA has higher than 50% PAE and 35.5 dBm output power in the band of 7.9 - 8.2 GHz. The measured linear power gain is 16.2 dB.